Mediation v. sulh: A comparative study - Mohd Zaki, Mohammad Hafiz; Termizi, Mazbah; Saleh, Muhammad Ridhwan; Mohd Din, Nina Syazmeen; Abu Hasan, Siti Farhana (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
One of the functions of law is for the settlement of dispute which led to the development of mediation and sulh in alternative dispute resolution (ADR) process. Mediation is a process whereby both parties intend to reach consensus in resolving a dispute through an agreement between the parties whereby mediator become an assistance in terms of communication and negotiation. Meanwhile, sulh can be defined as a harmonise way to settle dispute between the parties which consists of negotiation, mediation, conciliation and compromise of action. There are some similarities and differences between mediation and sulh that can be seen from the perspective of its legality, types of dispute, as well as their process and outcome. The advantages of mediation and sulh are clear in the dispute resolution. Therefore, this paper seeks to study the similarities and differences between mediation and sulh by comparing them from various perspectives.